Prevention Program in Anterior Cruciate Ligament (ACL) among Indonesian’s Athletes; Review Study - Made Vasundhari Putri Gayatri; I Dewa Made Ary Suandika; Komang Trisna Bayu Suta; Dellania Grandifolia Mustafa; Ni Kadek Yuni Fridayani; M. Widnyana; I Putu Gde Surya Adhitya (Physical Therapy Journal of Indonesia, 2022)
An ACL injury has been the most common injury for several years. Athletes and players who play the game have the same risk factor to have it. Injury prevention programs must be conducted among teams and could remove team injury costs in medical staff and rehabilitation. This review aims to conduct one prevention program for ACL injury in Indonesian soccer athletes. In Indonesia, this program needs support from all stakeholders, including the coach, chief executor manager, and the medical team. The risk factor of ACL injury is divided into external and internal factors, which have to be the main focus of the medical team to process a program. Prevention program for an ACL injury includes strengthening, agility, plyometrics, balance, and proper warm-up. Those types of exercise should be implemented in intervention among athletes, but they still need their perspectives and health condition.